Single-Ended Fast Protection for Transient Power of Multi-Terminal Flexible and Direct Power Grids Containing Renewable Energy - Shan, Jieshan; Tian, Xincui; Dai, Yue; Shu, Hongchun; Chang, Yong; Song, Jian (Frontiers in Energy Research, 2021)
With the proposal of the carbon peak goal, a multi-terminal flexible DC grid containing various renewable energy becomes the one of main ways of renewable energy power transmission. Thus, it is increasingly important to improve its transmission reliability and stability. This paper proposes a single-ended protection principle based on the analysis method of transient power change for the “mesh structure” ring-shaped flexible direct current (DC) grid. Based on the propagation characteristics of voltage, current, and anti-traveling waves during fault periods, the transient power variation coefficient based on SOD transformation is introduced to distinguish the internal and external faults. Besides, simulation based on the PSCAD/EMTDC platform within the Zhangbei four-port network verifies the effectiveness of the proposed protection principle under various fault conditions. Meanwhile, the protection criterion is designed according to the difference in the change coefficient of the transient power SOD within and outside the fault time zone. Moreover, the setting value of the start of protection is obtained by analyzing the simulation results, thus a set of fast and reliable single-ended protections for the same-side short-time transient power window of an enhanced flexible straight power grid is developed via combining it with the starting criterion of a sudden voltage change.